Answer:
A. (f-g)(x) = -7x -3
Step-by-step explanation:
(f -g)(x) = f(x) -g(x) = (-3x -5) -(4x -2)
= -3x -5 -4x +2
= -3x -4x -5 +2
(f -g)(x) = -7x -3
Answer:
6 years
Step-by-step explanation:
1.75% of 1,200 = 21
so 1 year= 21
21+21= 42 2 years
42+21=63 3 years
63+21=84 4 years
81+21=105 5 years
105+21=126 6 years
Or you can do
21x6=126 so it has to equal 6 years
I think the answer is 31.75
Answer:
53°
Step-by-step explanation:
It is given that the total measurement of the two angles combined would equate to 116°.
It is also given that m∠WXY is 10° more then m∠ZXY.
Set the system of equation:
m∠1 + m∠2 = 116°
m∠1 = m∠2 + 10°
First, plug in "m∠2 + 10" for m∠1 in the first equation:
m∠1 + m∠2 = 116°
(m∠2 + 10) + m∠2 = 116°
Simplify. Combine like terms:
2(m∠2) + 10 = 116
Next, isolate the <em>variable</em>, m∠2. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.
First, subtract 10 from both sides of the equation:
2(m∠2) + 10 (-10) = 116 (-10)
2(m∠2) = 116 - 10
2(m∠2) = 106
Next, divide 2 from both sides of the equation:
(2(m∠2))/2 = (106)/2
m∠2 = 106/2 = 53°
53° is your answer.
~